An assessment of different extraction and quantification methods of penta- and hexa-chlorobenzene from SRF fly-ash - Balampanis, Dimitris E.; Coulon, Frederic; Simms, Nigel J.; Longhurst, Philip J.; Pollard, Simon J. T.; Fenech, Cecilia; Villa, Raffaella (Elsevier, 2017)
Highly chlorinated benzenes, produced in the presence of organic matter and chlorine, are considered PCDD/Fs precursors, and are used as cost and time convenient substitute indicators for the indirect measurement of the latter. In this study penta- and hexa-chlorobenzene are quantified for the determination of the organochloride load of fly ash from solid recovered fuel incineration. Some of the chlorobenzenes are formed under ‘de novo’ conditions, through heterogeneous (ash particles/flue gases) reactions and are therefore deeply incorporated within fly ash. Accelerated solvent extraction (ASE) and ultrasonic solvent extraction (USE), along with the equivalent clean-up methods suggested by literature were compared to traditional Soxhlet. The extraction efficiencies achieved were 83 ± 7.5% for Soxhlet, 111 ± 19% for PFE, and 67 ± 17% for ultrasonication. Soxhlet extraction and clean-up through a multilayer silica gel column gave more precise results compared to the other sample preparation methods. Furthermore, performance comparison of gas chromatography fitted with either a mass spectrometer operated in single ion monitoring mode (GC-MS-SIM), or electron capture detector (GC- ECD) highlighted that ECD can be used for measuring chlorobenzenes traces down to 0.21 ng g−1, when the equivalent LOQ for MS-SIM was 3.26 ng g−1. The results further suggest that ECD can provide better peak integration than MS-SIM in the detection of chlorobenzenes in fly ash extracts, due to the detector's sensitivity to halogenated compounds.
Keywords: Organic halogens; Solvent extraction; Energy from waste; SRF; MBT